Integrating terminology management in developing student translators’ competence - Wulandari Simbolon; Yuli Audyani Hutajulu; Yesa Mutiara Sitompul; Jesika Bungaria Sinaga; Refika Andriani; Tatum Derin (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2026)
The current debate in translation pedagogy highlights the gap between learners’ general language proficiency and the demands of professional translation, particularly in maintaining terminological consistency. This study investigates how terminology management contributes to the development of student translators’ competence in technology-mediated translation contexts. A systematic literature review was conducted following the PRISMA framework, analyzing 23 selected studies published between 2021 and early 2026. The findings indicate that terminology management functions as an integrative competence connecting linguistic knowledge, technological literacy, and professional practice. Students’ difficulties in maintaining consistent terminology are often associated with limited terminological awareness and insufficient exposure to structured professional workflows, while corpus-based resources and AI-assisted technologies support both learning and evaluation. However, technological integration still requires critical human supervision when automated outputs are evaluated. These findings suggest that translation pedagogy, particularly in English language education and translator-training contexts, should prioritize structured terminology instruction supported by digital resources to better prepare students for professional translation practice.